Analisis Gerakan literasi sekolah (GLS) untuk meningkatkan keterampilan menulis peserta didik kelas V sekolah dasar - Adelia Trihandayani; Siti Istiyati; Anesa Surya (Didaktika Dwija Indria, 2024)
This research discusses the implementation of the School Literacy Movement (GLS) at SD Ta'mirul Islam Surakarta. This research uses a qualitative approach with a case study type to analyze the School Literacy Movement (GLS) in improving the writing skills of fifth grade students at SD Ta'mirul Islam Surakarta in 2023. Data collection techniques use observation, interviews and documentation. The GLS program includes team building, short, medium and long term program development, as well as a 15 minute reading activity before class. The school also provides an online library to make it easier for students and teachers to access it outside school hours. The writing skills of class V students can be seen through writing poetry and short stories, with themes involving characters, messages or book synopses. Learners are rewarded for their efforts, and facilities such as libraries provide significant support to the success of the GLS program. Ta'mirul Islam Elementary School produces outstanding students in the field of writing at national level whose work is published in the annual magazine. Teachers can implement the School Literacy Movement (GLS) to improve students' writing skills, while students can utilize literacy practices at school to improve their writing skills. The research results can also enrich knowledge about GLS in schools and become a reference for other researchers who are interested in similar topics. The research results can also be used as input for educators and students regarding literacy activities in schools to improve existing writing skills. Schools should provide special subjects or extracurricular writing as a place for students to develop their writing talents. This research can also be used as a reference for developing similar topics with the same variables.